Entrenching academic freedom through constructivist assessment activities during the COVID-19 pandemic - Sosibo, Z. C. (South African Journal of Higher Education, 2025)
When the COVID-19 pandemic forced learning institutions to shut their doors, many resorted to online teaching and learning (OTL) to observe social distancing meant to curb the spread of the virus. Due to the social isolation caused by OTL that substituted face-to-face teaching, students took control and actively engaged in their learning independent of support from their lecturers and peers. Therefore, COVID-19 catalysed self-directed learning (SDL) and constructivism. Research abounds on constructivism as an OTL approach during the pandemic. However, little is known about how constructivism was used to entrench academic freedom among students. This research paper investigated constructivist assessment activities that university instructors used during the COVID-19 pandemic and how they entrenched students’ academic freedom. The research question was: “What constructivist assessment activities did university instructors employ during the COVID-19 pandemic, and how did these activities foster students’ academic freedom?” Data were collected through open-ended questionnaires sent to a population of 45 lecturers in three teacher education programmes at a Faculty of Education at a university in the Western Cape Province of South Africa. Eighteen responses were received, and five were discarded because they did not address the questions asked. Emergent themes were generated through colour coding and thematic analysis. Results showed that assessment activities such as problem-based learning (PBL), e-portfolios, research, debates and discussions fostered different academic freedoms among students. The recommendation was that university instructors embrace constructivism in teaching, learning, and assessments, as it promises to be a liberating tool for students.